Evaluation of vestibular functions and balance in Edirne Band musicians - (:unkn) unknown (IOS PRESS, 2021)
BACKGROUND: It has been found that intense noise may affect the peripheral vestibular system and consequently causes problems in balance mechanisms. OBJECTIVE: The aim of this study was to investigate the effects of exposure to chronic noise on vestibular functions and balance in Edirne Band musicians. METHODS: Twenty-two individuals working in the Edirne Band for at least 5 years and a control group of 22 individuals working at Trakya University with similar sociodemographic characteristics were included. The socio-demographic questionnaire was used to inquire about the demographic characteristics of individuals, the ABC Scale to assess how they felt about the balance, and the DHI to determine the quality of life related to dizziness. A 3D ultrasonic system was used to assess the static and dynamic balance of the individuals. RESULTS: There was a statistically significant difference between the band and the control group in terms of longitudinal deviation and self-spin parameters of the Unterberger test, dizziness handicap inventory scores, functional balance according to activity-specific balance confidence scale (p < 0.05). CONCLUSIONS: As a result of our study, it has been shown that the balance, quality of life and vestibular system functions are negatively affected in the band exposed to noise for a long time.
Keywords: Noise; vestibular system; balance; quality of life; DIZZINESS HANDICAP INVENTORY; INDUCED HEARING-LOSS; CONFIDENCE SCALE; NOISE; EXPOSURE; SYSTEM